THU0302 Safety and efficacy of tocilizumab therapy in children with systemic onset of juvenile idiopathic arthritis. (23rd January 2014) - Alexeeva, E.; Denisova, R.; Valiyeva, S.; Bzarova, T.; Isayeva, K.; Sleptsova, T.; Mitenko, E.
Abstract : Background: The treatment of systemic onset of juvenile idiopathic arthritis (JIA is one of the serious problem of paediatric rheumatology, therefore development and implementation of new high-tech methods of treatment is relevant. Tocilizumab is promising drug for the treatment of systemic arthritis refractory to immunosuppressive drugs. Objectives: To evaluate safety and efficacy of tocilizumab treatment in children with systemic onset of juvenile idiopathic arthritis (JIA). Methods: A retrospective observational study on JIA patients taking tocilizumab (n=60). Tocilizumab was administered intravenously at a dose of 8 -10 mg/kg every 2 weeks during 2 months then every 4 weeks. All patients received DMARDs. Efficacy end points included the American College of Rheumatology (ACR) Pediatric 30 (Pedi 30), Pedi 50, Pedi 70, and Pedi 90 criteria for improvement. Results: A total of 60 patients (30 boys and 30 girls) were included in this Median age was 6, 5 years (range; 2 to 15 years) and median disease duration was 4, 5 years (range; 0.5 to 12 years). A total of 24 of the 60 patients (40%) entered 52 weeks of continuous tocilizumab treatment. The ACR Pedi 30, 50, 70 and 90 were achieved by 82%, 47%, 29% and 12% of patients at Week 4 (N=52), and by 100%, 90%, 65%, and 43% of patients at Week 24 (N=50), and by 100%, 100%, 75%, and 45% of patients at Week 52 (N=24), respectively.The frequently observed non-severe adverse events were nasopharyngitis, upper respiratory tract infection and gastroenteritis. No cases of opportunistic infections, malignancies, autoimmune diseases, or death were reported. Two cases of pneumonia and cellulytis. 25 patients had incidences of neutropenia. Conclusions: Clinical improvements in the signs and symptoms of systemic JIA were also achieved in favorable levels in tocilizumab in the treatment of children with JIA. Disclosure of Interest: None Declared